New Design of Triband Rectangular Printed Antenna With DGS for Mobile Communications (Journal of Informatics and Mathematical Sciences, 2021)
A new design of a rectangular printed antenna for mobile communication is presented in this paper. The material substrate chosen is Rogers 3003c \((ε r=3)\) and DGS (Defected Ground Structure) is used for bandwidth enhancement. The proposed antenna resonates over 900, 1800 and 2600 MHz frequencies for 2G/3G and 4G cellular phone. CST Microwave studio simulates the proposed rectangular printed antenna characteristics such as return loss S11, VSWR (voltage standing wave ratio), Gain and Radiation pattern.